2022
DOI: 10.1590/1980-549720220020.supl.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao óbito entre pacientes com câncer internados por COVID-19 em Mato Grosso, Brasil

Abstract: Objetivo: Analisar os fatores prognósticos para o óbito por COVID-19 em pacientes com câncer. Métodos: Estudo retrospectivo a partir dos dados registrados no sistema de notificação de casos de internações por COVID-19 de Mato Grosso. Foram avaliados casos notificados de COVID-19 internados entre abril de 2020 a junho de 2021 com câncer. Foram calculadas as frequências absolutas e relativas das variáveis sociodemográficas, de assistência hospitalar e comorbidades, assim como média, mediana e desvio-padrão da id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…14,15 . In relation to race/color, corroborating the present study, a higher frequency of brown and black people was observed 16,17,18 . With regard to sex, a higher frequency of women was observed in this study and it is believed that this data is due to the fact that the ICU of the hospital where the data were collected was a reference for the care of pregnant or postpartum women with Covid-19 in the state of Mato Grosso.…”
Section: Discussionsupporting
confidence: 92%
“…14,15 . In relation to race/color, corroborating the present study, a higher frequency of brown and black people was observed 16,17,18 . With regard to sex, a higher frequency of women was observed in this study and it is believed that this data is due to the fact that the ICU of the hospital where the data were collected was a reference for the care of pregnant or postpartum women with Covid-19 in the state of Mato Grosso.…”
Section: Discussionsupporting
confidence: 92%
“…Nesse estudo 18 , o óbito esteve associado à idade maior de 65 anos e tabagismo. Na presente análise, a maioria dos pacientes era maior de 60 anos e do sexo masculino, e essas características estiveram associadas a piores desfechos tanto em populações gerais 20 quanto em populações específicas de pacientes com câncer 21,22 . No entanto, idade e sexo não tiveram associação com o óbito, possivelmente pelo número pequeno de pacientes.…”
Section: Resultsunclassified